2017
DOI: 10.3389/fmicb.2017.02083
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Photogrammetry to Assess Lichen Colonization in the Hyper-Arid Namib Desert

Abstract: The hyper-arid central region of the Namib Desert is characterized by quartz desert pavement terrain that is devoid of vascular plant covers. In this extreme habitat the only discernible surface covers are epilithic lichens that colonize exposed surfaces of quartz rocks. These lichens are highly susceptible to disturbance and so field surveys have been limited due to concerns about disturbing this unusual desert feature. Here we present findings that illustrate how non-destructive surveys based upon advanced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Fog events are a known, documented and important water source for many species in the fog zone of the Namib Desert (Lange et al 1994, Mary Seely et al 2005, Lange et al 2006, Lange et al 2007, Ebner et al 2011 and the presence of extensive epiphytic lichen growth in the area of the near-coastal sites (Lange et al 1994, Lange et al 2006, Lange et al 2007, Hinchliffe et al 2017) is a strong indication that this area receives regular fog water input. However, previous research has found that, at a depth of 2 cm, no change in soil moisture can be associated with visible fog events (Warren-Rhodes et al 2006, Ebner et al 2011, Li et al 2018.…”
Section: Impact Of Fog Events On Soil Moisture Availabilitymentioning
confidence: 99%
“…Fog events are a known, documented and important water source for many species in the fog zone of the Namib Desert (Lange et al 1994, Mary Seely et al 2005, Lange et al 2006, Lange et al 2007, Ebner et al 2011 and the presence of extensive epiphytic lichen growth in the area of the near-coastal sites (Lange et al 1994, Lange et al 2006, Lange et al 2007, Hinchliffe et al 2017) is a strong indication that this area receives regular fog water input. However, previous research has found that, at a depth of 2 cm, no change in soil moisture can be associated with visible fog events (Warren-Rhodes et al 2006, Ebner et al 2011, Li et al 2018.…”
Section: Impact Of Fog Events On Soil Moisture Availabilitymentioning
confidence: 99%
“…This conclusion was recently supported by an extensive remote sensing drone survey of coastal Namib Desert lichen fields using advanced photogrammetry, which showed that Xanthoparmelia and Stellanrangia spp. preferentially colonized ocean-facing rock surfaces, i.e., the direction from which fog originates [ 62 ].…”
Section: Sources Of Bioavailable Water In Desert Ecosystemsmentioning
confidence: 99%
“…These 2D images can be taken with widely available commercial cameras (or those in mobile devices), rather than the dedicated equipment required for other 3D modeling approaches reviewed for natural history collections by Nieva de la Hidalga et al (2019) and Brecko and Mathys (2020). Because many cameras and their accessories have been designed to be mobile and for outdoor use, photogrammetry has been implemented widely in field conditions, providing insights into areas such as lichen colonization (Hinchliffe et al, 2017), the size of Weddell seals (Beltran et al, 2018), coral growth rates (Lange and Perry, 2020), and many others. Measurements of models produced via photogrammetry can be comparable to those from the physical subject, as demonstrated for plants in agricultural research studies (e.g., Gao et al, 2021), and to those from other modeling approaches, as demonstrated for skeletons by Giacomini et al (2019;compared with laser scanning and micro-computed tomography).…”
Section: Introductionmentioning
confidence: 99%